PENGARUH KECERDASAN EMOSIONAL DAN KOMPETENSI TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH MOTIVASI INTRINSIK PADA BADAN PERTANAHAN NASIONAL KOTA PEMATANG SIANTAR - Yessy Rifani; Murkhana Murkhana (Departemen Manajemen, 2023)
This study aims to determine the effect of Emotional Intelligence and Competence on Employee Performance Mediated by Intrinsic Motivation at the Badan Pertanahan Nasional Kota Pematang Siantar. This research is a quantitative research, collecting data using a questionnaire as an instrument. The population and respondents in this study were employees of the Badan Pertanahan Nasional Kota Pematang Siantar using the census method, totaling 76 people. The data analysis method used is Statistical Product and Service Solutions (SPSS). The results of the study found that emotional intelligence, competence, and intrinsic motivation directly affect employee performance. The results of the study also found that emotional intelligence and competence influence the mediator variable, namely intrinsic motivation, so that intrinsic motivation can become a mediator on emotional intelligence and competence on employee performance.